Developing Skills for Writing Geographically - Alam, Sarfaraz (National Geographical Journal of India, 2022)
Geography has evolved as a distinct field of enquiry. What are the grounds of its distinctiveness? Its distinctiveness is neither based on its subject matter nor on its methodology. On the contrary, it is the approach of dealing with the subject matter and the sorts of questions asked by geographers that lend geography a distinct identity of its own. Geographical approaches are ways of looking at the earth. Geographical questions are those which aim to elicit response about the spatial and ecological characteristics of the earth as a human habitat. Geographical questions are driven by action verbs. These verbs are used to extract specific thinking skills from students. This article is an attempt to present sy stematic definitions of some of the most commonly used action verbs in questions asked in geography examinations or questions given in geography textbooks. Students well versed with meanings of these action verbs may develop abilities of thinking and writing answers to geographical questions in a distinctly geographical way. Thinking and writing geographically require students to behold the earth as a human habitat.